Reversed flow injection spectrophotometric determination of chlorate - Thanyarat Chuesaard (2018)
An interfacing has been developed to connect a spectrophotometer with a personal computer and used as a readout system for development of a simple, rapid and sensitive reversed flow injection (rFI) procedure for chlorate determination. The method is based on the oxidation of indigo carmine by chlorate ions in an acidic solution (dil. HCl) leading to the decrease in absorbance at 610 nm. The decrease in absorbance is directly related to the chlorate concentration present in the sample solutions. Optimum conditions for chlorate were examined. A linear calibration graph over the range of 0.1-0.5 mg L-1chlorate was established with the regression equation of Y = 104.5X + 1.0, r2= 0.9961 (n = 6). The detection limit (3σ) of 0.03 mg L-1, the limit of quantitation (10σ) of 0.10 mg L-1and the RSD of 3.2% for 0.3 mg L-1chlorate (n = 11) together with a sample throughput of 92 h-1were obtained. The recovery of the added chlorate in spiked water samples was 98.5 ± 3.1%. Major interferences for chlorate determination were found to be BrO3-, ClO2-, ClO-and IO3-which were overcome by using SO32-(as Na2SO3) as masking agent. The method has been successfully applied for the determination of chlorate in spiked water samples with the minimum reagent consumption of 14.0 mL h-1. Good agreement between the proposed rFIA and the reference methods was found verified by Student's t-test at 95% confidence level. © 2009 Elsevier B.V. All rights reserved.